1997
DOI: 10.1111/j.1432-1033.1997.t01-1-00767.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the Proteoglycan Decorin

Abstract: Biosynthesis of decorin was investigated by incubating a rat fibroblast cell line with various radiolabelled protein and galactosaminoglycan precursors. The following cell-associated and distinct intermediates were isolated and identified: a pool of non-glycosylated core protein, two pools of decorin with incomplete chains, one with three sulphated disaccharide repeats and another with five or more sulphated disaccharide repeats, as well as decorin with mature chains. Results of pulsekhase experiments indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…The cell line, anti-(rat decorin), glycosaminoglycan, oligosaccharide and disaccharide standards, decorin proteoglycan and core protein, chondroitin lyases, prepacked columns and media, brefeldin A and proteinase inhibitors will be described in a forthcoming report (Moses et al, 1997). A linkage-region preparation from dermatan sulfate was prepared as described (Fransson, 1968).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell line, anti-(rat decorin), glycosaminoglycan, oligosaccharide and disaccharide standards, decorin proteoglycan and core protein, chondroitin lyases, prepacked columns and media, brefeldin A and proteinase inhibitors will be described in a forthcoming report (Moses et al, 1997). A linkage-region preparation from dermatan sulfate was prepared as described (Fransson, 1968).…”
Section: Methodsmentioning
confidence: 99%
“…In work described in a report to be published shortly (Moses et al, 1997), we studied early steps in galactosaminoglycan assembly in a rat fibroblast cell line that synthesizes and secretes decorin. By using an antiserum directed against the core protein we detected three pools of intermediates substituted with the linkage region plus either three or five or more sulfated repeats or with a mature chain.…”
mentioning
confidence: 99%
“…Recent simultaneous analysis of both CS and HS chains of the hybrid type proteoglycan syndecan-1 molecule has suggested the Xyl phosphorylation of both CS and HS chains (34). Structural analysis of the biosynthetic intermediate oligosaccharides formed in the cultured rat fibroblasts has suggested that dephosphorylation takes place soon after the transfer reaction of GlcUA to the trisaccharide (57)(58)(59). In vitro enzyme assays using crystallized human glucuronyltransferase I as enzyme (60) and Gal-Gal-Xyl(2-O-phosphate)-Ser as acceptor have demonstrated the higher enzyme activity with the phosphorylated acceptor substrate.…”
Section: Disaccharidesmentioning
confidence: 99%
“…These differences in molecular size appear to derive primarily from the differences in the sulfation and length of glycosaminoglycan chains of PGs in each fraction. Although the length of glycosaminoglycan chains was not determined in this study, the undersulfated and nonsulfated glycosaminoglycan chains of PGs in Fractions 1 and 2 appear to be shorter than those in Fraction 3, because the differences between the elution positions on chromatographies are too great to be accounted for only by the extent of sulfation; furthermore, it has been reported that the sulfation of the glycosaminoglycan chain occurs during its polymerization 28,29) and that the glycosyltransferases involved in the chain elongation have higher activity toward the sulfated oligosaccharides than toward the nonsulfated ones 30,31) (the sulfation could be a rate-limiting step of the chain elongation). The results described above are consistent with those reported by Funderburgh et al 21) and Schrecengost et al 22) The chromatographies in this study also show, however, that PGs with short, highly sulfated and long, nonsulfated glycosaminoglycan chains were present in both organ and cell cultures.…”
Section: Discussionmentioning
confidence: 71%